2020
DOI: 10.1111/1365-2664.13593
|View full text |Cite
|
Sign up to set email alerts
|

Classical biological control and apparent competition: Evaluating a waterhyacinth invaded community module

Abstract: 1. The scope and complexity of interactions within community food webs necessitates their simplification to a community module scale for conducting empirical studies. An outdoor mesocosm study in the USA quantified the strengths of direct and indirect interactions between two herbivore congeners that fed on two aquatic plant species while sharing a parasitoid.2. Kalopolynema ema (Hymenoptera: Mymaridae) is a stenophagous native egg parasitoid that attacks the hemipteran species in this study, Megamelus davisi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…Although native parasitoids are known to utilise M. scutellaris in its extant range, overall parasitism is relatively low (Minteer et al 2016). Tipping et al (2020) found no evidence of apparent competition between M. scutellaris and M. davisi, a native planthopper with the shared native parasitoid Kalopolynema ema (Schauff and Grissell) (Hymenoptera: Mymaridae) in Florida. Although parasitism has never been documented as the cause of a biological control agent species failing to establish, it has been shown to reduce their effectiveness (Paynter et al, 2010).…”
Section: Introductionmentioning
confidence: 87%
“…Although native parasitoids are known to utilise M. scutellaris in its extant range, overall parasitism is relatively low (Minteer et al 2016). Tipping et al (2020) found no evidence of apparent competition between M. scutellaris and M. davisi, a native planthopper with the shared native parasitoid Kalopolynema ema (Schauff and Grissell) (Hymenoptera: Mymaridae) in Florida. Although parasitism has never been documented as the cause of a biological control agent species failing to establish, it has been shown to reduce their effectiveness (Paynter et al, 2010).…”
Section: Introductionmentioning
confidence: 87%
“…The Invasive Plant Research Laboratory (IPRL) in Fort Lauderdale, FL, is quantitatively evaluating the benefits of biological control agent impacts on weed populations, such as water hyacinth [ Eichhornia crassipes (Mart.) Solms], A. philoxeroides , and Brazilian peppertree ( Schinus terebinthifolius Raddi), for invaded plant communities in riparian, wetland, and terrestrial ecosystems (McEvoy et al 2012), and the occurrence of “indirect effects” of released agents on trophic food webs (Tipping et al 2020). Much work is now underway by the IPRL, along with the Invasive Species and Pollinator Health Research Unit (ISPHRU) in Albany, CA, and the Pest Management Research Unit (PMRU) in Sidney, MT, in several areas, including advances in molecular tools to identify agents and pinpoint host provenance and for other applications; broad ecological examinations, including response to changes in climate; and utilization of novel tools to ask wide-ranging questions.…”
Section: Present—ars Weed Science Researchmentioning
confidence: 99%
“…Increasingly, in addition to temperature-dependent biology studies, range modeling based on those responses and presence/absence data is also being used to predict how populations will not only expand once released, but might shift in response to changes in temperature (Sánchez-Guillén et al 2016). For example, IPRU scientists demonstrated that the presence of a shared parasitoid had no impact on a native congener, but this example of unrealized indirect effects may shift if plant chemistries change (Tipping et al 2020). Many of these plant-insect-parasitoid interactions are indirect, interacting, and context dependent, emphasizing the need for larger-scale investigations for the impacts of global change drivers on biological control agents and their hosts.…”
Section: Iwm In Cropping Systemsmentioning
confidence: 99%